Optimization of the cross section area on the meridian surface of the 1400-MW canned nuclear coolant pump based on a new medial axial transform design method. (May 2018) - Wang, Xiaofang; Lu, Yeming
Abstract: Canned coolant pump is the only rotating part of the nuclear island, which provides continuous power for the medium circulation. Therefore, new innovative approaches to improve the pump's performances are of great significance. To adjust the hub and shroud profiles spontaneously and control the scale of the design parameters effectively, a special investigation about optimizing the distribution of the cross section area on the meridian surface would be done here. In order to represent the meridian shape accurately with the corresponding expected cross section area distribution, the new design strategy established on the Media Axis Transform (MAT) design theory was presented firstly. Then with the integration of the new meridian design approach, Computational Fluid Dynamic (CFD) analysis, Central Composite Design (CCD), Respond Surface Method (RSM) and Non-nominated Sorting Genetic Algorithm-II (NSGA-II), an optimization system was ultimately established. Taking the scale model of CAP1400 (on a scale of 1:2.5) as the reference, the optimal cross section area distribution was gotten successfully after the optimization. Ultimately, the optimal distribution of the cross section area was obtained, and through CFD analysis and inner flow analysis, it can be found that the performances of the optimal sample are improved in relative to the reference model from 0.8Qd to 1.2Qd . Most importantly, at the design point, the increasement of efficiency is 1.7%, while the head improvement is about 2.6%. The study here is expected to provide a new strategy for the meridian surface optimization of the large-scale turbomachinery with front and rear matching parts.